Large‐scale white matter network reorganization in posttraumatic stress disorder - Suo, Xueling (Hum Brain Mapp, 2019)
Recently, graph theoretical approaches applied to neuroimaging data have advanced understanding of the human brain connectome and its abnormalities in psychiatric disorders. However, little is known about the topological organization of brain white matter networks in posttraumatic stress disorder (PTSD). Seventy‐six patients with PTSD and 76 age, gender, and years of education‐matched trauma‐exposed controls were studied after the 2008 Sichuan earthquake using diffusion tensor imaging and graph theoretical approaches. Topological properties of brain networks including global and nodal measurements and modularity were analyzed. At the global level, patients showed lower clustering coefficient (p = .016) and normalized characteristic path length (p = .035) compared with controls. At the nodal level, increased nodal centralities in left middle frontal gyrus, superior and inferior temporal gyrus and right inferior occipital gyrus were observed (p < .05, corrected for false‐discovery rate). Modularity analysis revealed that PTSD patients had significantly increased inter‐modular connections in the fronto‐parietal module, fronto‐striato‐temporal module, and visual and default mode modules. These findings indicate a PTSD‐related shift of white matter network topology toward randomization. This pattern was characterized by an increased global network integration, reflected by increased inter‐modular connections with increased nodal centralities involving fronto‐temporo‐occipital regions. This study suggests that extremely stressful life experiences, when they lead to PTSD, are associated with large‐scale brain white matter network topological reconfiguration at global, nodal, and modular levels.